Strategi Bisnis Rumah Sakit Non-JKN dalam Menghadapi Dinamika Pasar Era JKN - Pande Putu Adnyani; Putu Purnama Dewi (Jurnal Riset Akuntansi, 2026)
The implementation of the National Health Insurance Program has transformed the competitive dynamics of the healthcare industry in Indonesia, particularly for non-JKN private hospitals. This study aims to analyze the business strategies implemented by non-JKN hospitals in responding to market changes during the JKN era. The research employed a qualitative approach with a case study design involving four non-JKN hospitals in Bali, namely BIMC Hospital Kuta, BIMC Hospital Nusa Dua, Kasih Ibu General Hospital Denpasar, and RSIA Bunda Denpasar. Data were collected through in-depth interviews, observations, and documentation studies, and were analyzed inductively through data reduction, categorization, data presentation, and conclusion drawing. The findings reveal that non-JKN hospitals primarily adopt a differentiation focus strategy to maintain competitiveness. This strategy is reflected in premium healthcare services, faster service delivery, direct access to specialist doctors, medical tourism development, utilization of modern medical technology, and personalized patient care. The study also finds that the integration of SWOT analysis, Porter’s generic strategies, and the Balanced Scorecard supports more adaptive and sustainable business strategy implementation. Strategic success is determined by adaptive leadership, service innovation, human resource development, and the hospitals’ ability to respond to changing consumer behavior and market competition. This research confirms that non-JKN hospitals still possess significant market opportunities through service quality enhancement and premium patient segmentation amid the dominance of the JKN system.